EVALUATION OF IMPORTANCE FOR RESEARCH IN EDUCATION - PRAMODINI D V, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
An evaluation of research in education, with the general aim of systematically, improving an academic body of knowledge may deficits in systems be highlighted by well designed research. The results of research can lead (ideally) to changes in methods or practices (in the case of education it might be a teaching methods, say online Vs in class on campus). This would ideally appropriate education is provided to the students resulting in a more effective/efficient population. This paper explores different senses of the concept of meaning in educational research, presenting ‘meaning’ as personal (the researcher’s quest for meaning through research), contextual (meaning in relation to linguistics and culture) and shared (through communication), offering the various types, challenges, benefits and forms of research in practice-based research in educational technology.